Answer:
Choice a is correct answer.
Explanation:
Given equation is :
x²-4x-9 = 29
Adding -29 to both sides of above equation , we get
x²-4x-9-29 = -29+29
x²-4x-38 = 0
ax²+bx+c = 0 is general quadratic equation .
Comparing given equation with quadratic equation , we get
a = 1 , b = -4 and c = -38
x = (-b±√b²-4ac) / 2a
Putting above values in quadratic equation, we get
x = ( -(-4) ± √(-4)²-4(1)(-38) ) / 2(1)
x = ( 4±√16+152) / 2
x = ( 4± √168) / 2
x = (4±√4×42) / 2
x = (4±2√42) / 2
taking 2 common, we get
x = 2( 2±√42) / 2
x = 2±√42 which is the answer.